Completeness of Prescription Contributes to Prescribing Errors in Hospitals: Is this the Doctor's Negligence? - Shely Oktavia Puspita Ningrum; Mardhina Ratna Prabasari; Djazuly Chalidyanto (Wolters Kluwer - Medknow Publications, 2022)
Introduction: Incident reporting is the primary key to implement patient safety. One indicator of patient safety is to reduce prescription errors. Errors in writing prescriptions can cause the treatment process to be disrupted and even lead to malpractice and ethical violations. This study aimed to know the effect of individual and organizational factors on prescribing errors in the Outpatient Unit of Nganjuk Public Hospital. Methods: This research was a cross-sectional observational study in the Outpatient Clinic of Nganjuk State General Hospital. This study used a questionnaire and prescriptions with a total sample of 362 prescriptions from 24 doctors, with exclusion criteria: doctors with an expired license at the time of the study and doctors with <2 years of service. Prescriptions were also used as a sample to assess the incidence of prescribing errors. This research used descriptive analysis with cross-tabulations. Results: A doctor's knowledge about writing complete prescriptions is the most related factor to prescribing errors (n = 0.159) in individual factors. Likewise, the doctor's perception variable related to prescribing policy has the most substantial relationship compared to other variables on organizational factors (n = 0.235). Conclusions: Several factors influence prescribing errors, such as the physician's skill and knowledge. Doctors with high subjective and objective workloads, doctors' perceptions regarding the incident reporting system, prescribing policies, and medication management also affect prescribing errors. Training and reduction of doctors' workload could be the solution to reduce prescribing errors.